Analisis Dampak Negatif Penggunaan Gadget dalam Pengembangan Sosial dan Emosional Siswa Kelas IV Sekolah Dasar Negeri XV Desa Sungai Bengkal Kabupaten Tebo - Irda Afrahima; Mislan Mislan (Universitas Palan, 2025)
This research focuses on discussing the Analysis of the Negative Impact of Using Gadgets in the Social and Emotional Development of Class IV Students at XV State Elementary School, Sungai Bengkal Village, Tebo Regency. This research uses a qualitative descriptive approach. The data collection techniques in this research are observation, interviews and documentation. Related to the data analysis techniques that researchers use, namely data editing, data presentation and drawing conclusions. The aim of this research is to determine the negative impact of using gadgets on the social and emotional development of students at the XV Elementary School in Sungai Bengkal Village, Tebo Regency. The results of this research show that the negative impacts of gadget use on students at State Elementary School XV, Sungai Bengkal Village, Tebo Regency include social and emotional development disorders. Students show decreased ability for face-to-face social interaction, difficulty managing emotions, and increased stress levels. Uncontrolled online content is also a risk factor. Therefore, comprehensive intervention and collaboration between schools, parents and students is needed to overcome this problem.